PROBLEMS IN THE ACTIVITIES OF THE LOWER HOUSE OF PARLIAMENT TO ENSURE NATIONAL SECURITY (Scientific journal of the Fergana State University, 2025)
The article discusses such issues as the functions of representation, legislation and control of parliament, analysis of legislative acts on this subject and issues related to security, opinions of leading scientific circles, the experience of foreign countries, the legislative initiative of the Committee on Defense and Security, the main task facing parliament, the mechanism for ensuring the information and analytical aspect, control and analytical measures and goals.